Persistence of scrapie infectivity within a farm environment after cleaning and decontamination - Hawkins, Steve A.C.; Simmons, Hugh A.; Gough, Kevin C.; Maddison, Ben C. (BMJ Publishing Group, 2015)
Scrapie of sheep/goats and Chronic Wasting Disease (CWD) of deer/elk are contagious prion diseases where environmental reservoirs are directly implicated in the transmission of disease. In this study the effectiveness of recommended scrapie farm decontamination regimes was evaluated by a sheep bioassay using buildings naturally contaminated with scrapie. Pens within a farm building were treated with either 20,000ppm free chorine solution for one hour, or were treated to same but were followed with painting and full re-galvanisation or replacement of metalwork within the pen. Scrapie susceptible lambs of the PRNP genotype VRQ/VRQ were reared within these pens and their scrapie status was monitored by RAMALT. All animals became infected over an 18-month period, even in the pen that had been subject to the most stringent decontamination process. This data suggests that recommended current guidelines for the decontamination of farm buildings following outbreaks of scrapie do little to reduce the titre of infectious scrapie material and that environmental re-contamination could also be an issue associated with these premises.